Embedding English Language Across the Curriculum in Higher Education: A Continuum of Development Support - Briguglio, Carmela; Watson, Shalini (Lythrum Press, 2014)
The intensification of internationalisation and associated massification of higher education implies the need for universities to accommodate the diverse learning needs of increasingly heterogeneous student cohorts. Consequently, skills in English as a second or additional language (ESL/EAL) need to be developed through personal student initiative and/or deliberate intervention in teaching and learning. This paper argues that the ‘international university’ should provide a variety of avenues for student language development, ranging from student self-access strategies to language support that is totally embedded in the curriculum. A Multi-layered Model of Language Development Provision (the MMLDP) is presented, and the implications and effectiveness of the different provisions are discussed.